Feasibility of a cognitive strategy training intervention for people with Parkinson's disease. Issue 10 (8th May 2018) - Foster, Erin R.; Spence, Daniel; Toglia, Joan
Abstract: Purpose: To investigate the feasibility of a novel client-centered cognitive strategy training intervention for people with Parkinson's disease (PD). Materials and methods: This was a case series of seven people with PD without dementia but with subjective cognitive decline. The intervention involved ≥5 treatment sessions at the participant's home. Participant acceptance and engagement were assessed by the Credibility/Expectancy Questionnaire (CEQ), Client Satisfaction Questionnaire (CSQ), enjoyment and effort ratings, and homework completion. Logistical information was tracked, and the Canadian Occupational Performance Measure (COPM) was an exploratory outcome measure. Data analysis was descriptive. Results: CEQ scores were positive and increased over time. CSQ scores were high ( M = 30.8, SD = 0.75), with all participants rating all items positively. Almost all (95%) effort and enjoyment ratings were ≥3 (Much), and homework completion rates averaged 84% ( SD = 18). Intervention duration was 6–15 weeks ( M = 9.2, SD = 2.8), with treatment sessions averaging 1.7 h ( SD = 0.5). Group and most individual COPM ratings improved ≥2 points. Conclusions: These findings support the feasibility of the intervention for people with PD. It was acceptable, engaging, and promising in terms of its effect on self-identified functional cognitive problems. Implications for Rehabilitation: People with Parkinson's disease (PD) without dementia can experience cognitive decline that negatively impacts function and quality of life. Strategy-based interventions that explicitly train for transfer may mitigate the negative functional consequences of cognitive decline in this population. We developed a client-centered cognitive strategy training intervention for people with PD. This small case series supports its feasibility, indicating that it is acceptable and engaging for people with PD and promising in terms of its effect on self-identified functional cognitive problems.